The Yin and Yang of traditional Chinese and Western medicine. Issue 6 (18th February 2021) - Fu, Rao; Li, Jie; Yu, Huatao; Zhang, Yang; Xu, Zhihong; Martin, Cathie
Abstract: The success of Western Scientific approaches to medicine, over the last 150 years, can be measured by substantial increases in life expectancy, reductions in infant mortality and the virtual elimination of many infectious diseases accompanied by development of effective management practices for noncommunicable diseases. However, major challenges remain in the form of infectious diseases that evolve resistance to pharmaceuticals rapidly, new diseases, particularly those caused by viruses and effective long‐term treatments for chronic, noncommunicable diseases. Traditional Chinese Medicine (TCM) can offer complementary treatments based on personalised interventions, informed by knowledge accumulated from empirical observations gathered over centuries of practice, that address the impact of disease on the whole body. We provide examples of both infectious and noncommunicable diseases where the combination of Western Scientific Medicine (WSM) and TCM can benefit patients in terms of the speed and efficacy of recovery or disease management. TCM is a healing skill based on practice, while WSM is scientific, based on experiments. Against this background, an understanding of the mechanisms of action of traditional Chinese medicinal preparations will offer fresh routes to discovery and development of new therapeutics as well as patented medical prescriptions, which will rely heavily on modern scientific methodologies for their adoption and success, particularly those in plant genomics, plant breeding and synthetic biology.